Descriptive Study of The Concept of Islamic Education from a Women's Perspective (Rohana Kudus, Rahmah El-Yunusiyah, Rasuna Said, And Siti Walidah) - Pratiwi, Sekar Harum; Kustati, Martin; Sepriyanti, Nana (Journal International Inspire Education Technology, 2024)
This research is motivated by the problems that occur among women who are still hindered by the world of education. The researcher discusses how female figures in ancient times fought for the right to education for women. Therefore, the researcher discusses Islamic education during the time of Rohana Kudus, Rahmah El Yunusiyah, Rasuna Said, and Siti Walidah. The aim of this research is for readers to know about the struggles of the figures to raise the status of women in that era. This research uses the SLR (Systematic Literature Review) method. Data collection was carried out by systematically identifying journals and books related to the research topic.